Microvascular Compressicaude by Slinging a Tortuous Vertebrobasilar Artery to the Petrous Dura in Hemifacial Spasm: Technical Note - Chowdhury, Forhad Hossain; Haque, Mohammod Raziul; Rumi, Jalal Uddin Mohammod; Reza, Monir Hossain (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2018)
Objective In cases of hemifacial spasm caused by a tortuous vertebrobasilar artery (TVBA), the traditional treatment technique involves Teflon (polytetrafluoroethylene), which can be ineffective and fraught with recurrence and neurological complications. In such cases, there are various techniques of arteriopexy using adhesive compositions, ‘suspending loops’ made of synthetic materials, dural or fascial flaps, surgical sutures passed around or through the vascular adventitia, as well as fenestrated aneurysmal clips. In the present paper, we describe a new technique of slinging the vertebral artery (VA) to the petrous dura for microvascular decompression (MVD) in a patient with hemifacial spasm caused by a TVBA.Method A 50-year-old taxi driver presented with a left-sided severe hemifacial spasm. A magnetic resonance imaging (MRI) scan of the brain showed a large tortuous left-sided vertebral artery impinging and compressing the exit/entry zone of the 7th and 8th nerve complex. After a craniotomy, a TVBA was found impinging and compressing the entry zone of the 7th and 8th nerve complex. Arachnoid bands attaching the artery to the nerve complex and the pons were released by sharp microdissection. Through the upper part of the incision, a 2.5 × 1 cm temporal fascia free flap was harvested. After the fixation of the free flap, a 6–0 prolene suture was passed through its length several times using the traditional Bengali sewing and stitching techniques to make embroidered quilts called Nakshi katha. The ‘prolenated’ fascia was passed around the compressing portion of the VA. Both ends of the fascia were brought together and stitched to the posterior petrous dura to keep the TVBA away from the 7th and 8th nerves and the pons.Result The patient had no hemifacial spasm immediately after the recovery from the anesthesia. A postoperative MRI of the brain showed that the VA was away from the entry zone of the 7th and 8th nerves.Conclusion The ‘prolenated’ temporal fascia slinging technique may be a very good option of MVD in cases in which the causative vessel is a TVBA.
Keywords: hemifacial spam; microvascular decompression slinging of the vertebral artery; arteriopexy to the petrous dura